A Buffer Stock Model to Ensure Price Stabilization and Availability of Seasonal Staple Foods under Free Trade Considerations - Sutopo, Wahyudi; Bahagia, Senator Nur; Cakravastia, Andi; Arisamadhi, T.M.A. (ITB Journal Publisher, LPPM ITB, 2012)
PriceÂ volatilityÂ andÂ scarcityÂ haveÂ becomeÂ aÂ greatÂ problemÂ inÂ the distributionÂ systemÂ ofÂ seasonalÂ stapleÂ foodsÂ producedÂ byÂ theÂ agricultural industry.Â ThereÂ isÂ aÂ salientÂ supplyÂ disparityÂ duringÂ theÂ harvestÂ andÂ planting seasons.Â ThisÂ conditionÂ couldÂ causeÂ disadvantagesÂ toÂ stakeholdersÂ suchÂ as producers,Â wholesalers,Â consumers,Â andÂ government.Â ThisÂ paperÂ proposesÂ a bufferÂ stockÂ modelÂ underÂ free-tradeÂ considerationsÂ toÂ substituteÂ quantitative restrictionsÂ andÂ tariffsÂ withÂ anÂ indirectÂ marketÂ interventionÂ Â instrument.Â This instrumentÂ wasÂ developedÂ usingÂ aÂ bufferÂ stockÂ schemeÂ inÂ accordanceÂ with Â a Â warehouse receipt systemÂ (WRS) andÂ aÂ collateral management system.Â AÂ public serviceÂ institutionÂ forÂ stapleÂ foodÂ bufferÂ stockÂ Â (BLUPP)Â isÂ proposedÂ asÂ the wholesalerâs competitor,Â withÂ as main responsibilityÂ Â to ensure price stabilization and availability of staple food. Multi-criteria decision-making is formulated as a singleÂ objectiveÂ mixedÂ integerÂ non-linearÂ programmingÂ (MINLP)Â model.Â The resultsÂ showsÂ thatÂ theÂ proposedÂ modelÂ canÂ beÂ appliedÂ toÂ solveÂ theÂ distribution problemÂ andÂ canÂ giveÂ moreÂ promisingÂ outcomesÂ thanÂ itsÂ counterpart,Â direct market intervention.